All-Printed Thin-Film Transistor Based on Purified Single-Walled Carbon Nanotubes with Linear Response. (4th August 2011) - Gu, Guiru; Ling, Yunfeng; Liu, Runyu; Vasinajindakaw, Puminun; Lu, Xuejun; Jones, Carissa S.; Shih, Wu-Sheng; Kayastha, Vijaya; Downing, Nick L.; Han, Xuliang; Subbaraman, Harish; Pham, Dan; et al.
Abstract : We report an all-printed thin-film transistor (TFT) on a polyimide substrate with linear transconductance response. The TFT is based on our purified single-walled carbon nanotube (SWCNT) solution that is primarily consists of semiconducting carbon nanotubes (CNTs) with low metal impurities. The all-printed TFT exhibits a high ON/OFF ratio of around 10 3 and bias-independent transconductance over a certain gate bias range. Such bias-independent transconductance property is different from that of conventional metal-oxide-semiconductor field-effect transistors (MOSFETs) due to the special band structure and the one-dimensional (1D) quantum confined density of state (DOS) of CNTs. The bias-independent transconductance promises modulation linearity for analog electronics.